2022
DOI: 10.1007/s12672-022-00469-2
|View full text |Cite
|
Sign up to set email alerts
|

CENPO regulated proliferation and apoptosis of colorectal cancer in a p53-dependent manner

Abstract: Colorectal cancer (CRC) is considered to be a leading cause of cancer-related death. Centromere protein O (CENPO) can prevent the separation of sister chromatids and cell death after spindle injury. Nevertheless, the role of CENPO in CRC has not been reported. The expression level of CENPO in CRC was revealed by TCGA database and immunohistochemical (IHC) staining. Subsequently, the loss-of-function assays were performed to identified the role of CENPO in CRC in vitro and in vivo. Our data demonstrated that CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Studies have reported that the knockdown of CENPO inhibited GC cell growth, induced apoptosis, and decreased the expression of ATM, cyclin D1, and c-Jun [12]. Knockdown of CENPO in CRC downregulated the expression of N-cadherin, Vimentin, Snail, and CCND1, inhibited cell proliferation, and attenuated migration and invasion [15]. This is consistent with our Bioinformatics Analysis, the functional enrichment results showed signi cant enrichment of cell cycle, P53 pathway, and extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that the knockdown of CENPO inhibited GC cell growth, induced apoptosis, and decreased the expression of ATM, cyclin D1, and c-Jun [12]. Knockdown of CENPO in CRC downregulated the expression of N-cadherin, Vimentin, Snail, and CCND1, inhibited cell proliferation, and attenuated migration and invasion [15]. This is consistent with our Bioinformatics Analysis, the functional enrichment results showed signi cant enrichment of cell cycle, P53 pathway, and extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…High CENPO expression promotes the proliferation of gastric cancer cells and is positively associated with poor prognosis in gastric cancer [12]. CENPO is highly expressed in CRC tissues and cells as positively associated with the malignancy of CRC degree and positively correlated with tumor progression possibly through EMT and PI3K/AKT signaling pathways [15]. CENPO upregulation promoted bladder cancer progression [16].…”
Section: Introductionmentioning
confidence: 99%
“…[ 34 ] Studies have also shown that upregulation of CENPO may lead to bladder cancer and may depend on P53 to regulate the development, proliferation and apoptosis of colorectal cancer. [ 35 , 36 ] Studies have suggested that the high expression of CENPO has an adverse effect on the survival of breast cancer and leads to poor prognosis. It is also considered that CENPO is an independent factor affecting the distant recurrence survival rate of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the CENPO protein results in aneuploidy and aneuploidy chromosomal gains, which can lead to the development of disease or cancer [ 9 ]. Recent studies have shown that the alteration of CENPO expression has been found to contribute to the development of gastric cancer and colorectal cancer [ 10 , 11 ]. The mechanism of CENPO in bladder cancer may involve mitosis and complement as well as coagulation cascade signaling pathways [ 12 ].…”
Section: Introductionmentioning
confidence: 99%